Effects of ethanol on Oenococcus oeni - Silveira, Maria Graca da (Wageningen Universiteit, 2003)
Flow cytometric assessment of membrane integrity of ethanol-stressed cells of Oenococcus oeni, membrane fluidity adjustments in ethanol-stressed oenococcus oeni cells,...